Exploring the impact of social media engagement on brand image and brand love among senior tourists: The mediating role of emotional attachment and the moderating effect of digital literacy - Tongxi Jiang; Hasnizam Hasan; Azanin Ahmad (Innovative Marketing)
Type of the article: Research Article AbstractThis study aims to explore the impact of social media engagement on brand image and brand love among senior tourists in Jiangsu Province, China. Additionally, the study investigates the mediating role of emotional attachment and the moderating role of digital literacy in shaping these relationships. A cross-sectional survey was conducted between August and September 2024 in Jiangsu Province, China, targeting 300 senior tourists aged 60 and above who were active users of social media and had recent interactions with tourism-related brands. Data were collected using a structured questionnaire and analyzed using SmartPLS 4. The results indicate that social media engagement has a strong positive effect on both brand image (β = 0.598, t = 8.850, p < 0.001) and brand love (β = 0.352, t = 4.309, p < 0.001). Emotional attachment significantly mediates the relationship between social media engagement and brand outcomes, including brand image (β = 0.071, t = 2.162, p = 0.015) and brand love (β = 0.172, t = 3.935, p < 0.001). Moreover, digital literacy moderates the effect of social media engagement on emotional attachment (β = 0.155, t = 5.855, p < 0.001), indicating that higher digital proficiency enhances emotional bonding with brands. These findings underscore the importance of personalized, emotionally resonant, and accessible digital marketing strategies when targeting the senior tourism segment.